The prevalence of ALK rearrangement in pulmonary adenocarcinomas in an unselected Caucasian population from a defined catchment area: impact of smoking. Issue 6 (9th February 2017) - Skov, Birgit G; Clementsen, Paul; Larsen, Klaus R; Sørensen, Jens B; Mellemgaard, Anders
Abstract : Aims: To assess the prevalence of EML4–ALK rearrangement gene measured by immunohistochemistry in an unselected population‐based consecutive cohort of patients with adenocarcinoma of the lung (ACL), and the correlation with smoking history, thyroid transcription factor 1 (TTF1), gender and age. Methods and results: All patients diagnosed in the population of the greater Copenhagen area were included, irrespective of gender, age, smoking habits, stage or type of available diagnostic material. Tumours were stained with immunohistochemistry (clone 5A4). Immunohistochemistry‐positive tumours were tested by fluorescence in‐situ hybridization (FISH). During a 16‐month period, 760 patients in the population were diagnosed with ACL. In 2.6% there was insufficient material for ALK testing (20 of 760). Eleven per cent of the remaining 740 ACL patients were never smokers, 43% were ex‐smokers smokers and 46% were current smokers. Fourteen patients [1.9%, 95% confidence interval (CI) = 1.1–3.2] were ALK‐positive by immunohistochemistry. Nine of 82 never‐smokers (11%, 95% CI = 5.9–19.6) and five of 652 ex‐ or current smokers (0.8%, 95% CI = 0.4–2.1) were ALK‐positive. Only two ALK‐positive patients were found among 586 heavy smokers (> 15 pack‐years) (0.3%, 95% CI = 0.09–1.2). Thirteen of the 14 immunohistochemistry‐positive patients were FISH‐positive. All ALK‐positive tumours were TTF1‐positive. The number needed to test (NNT) to identify one ALK positive patient was 9, 22 and 293 among never smokers, light and heavy smokers, respectively. Conclusions: Immunohistochemical analysis of ALK rearrangement was possible in 97.4% of patients. ALK rearrangement was found primarily in never smokers. NNT to identify one ALK‐positive patient was 9, 22 and 293 among never smokers, light and heavy smokers, respectively.